Fluoride and Trace Elements in Tea: Oral and General Health - Faiez Hattab (Faculty of Dentistry, Universitas Trisakti, 2023)
Background: Tea is one of the most commonly consumed beverages. The main varieties of tea are black tea, green tea, and oolong tea produced from Camellia sinensis plant. Objective: The purpose of this study was to determine fluoride (F) and other elements in commercially available black and herbal tea products and to evaluate their benefits and safety. Methods: Chinese and Indian black teas and herbal tea (in bags or loose) were purchased from Hong Kong supermarkets. The tea infusion was prepared by adding 1 gram of tea leaves to 100 mL of deionized water preheated to 85oC. Samples were taken at regular intervals and analyzed for F, using the F− electrode. Trace elements in tea infusion was assessed using atomic absorption spectrophotometry. Results: Fluoride concentrations in infused 15 brands of Chinese tea ranged from 0.78 to 3.46 ppm (mg/L), with a mean of 1.73 ± 0.73 (SD). The corresponding values for 11 Indian teas ranged from 0.73 to 1.91, with a mean of 1.24 ± 0.32. In 6 herbal teas, the F concentration is almost negligible. The total F content in tea leaves ranged from 82 to 371 mg/kg. During 5 to 15 minutes of brewing, the mean (± SD) F released was 83.6 ± 12.1% of the total F in the leaves. Conclusions: Tea is a homogeneous, complex solution of bioactive organic and inorganic ingredients that benefits oral and systemic health. It has a higher F content than any other plant. Drinking tea in moderation, F is unlikely to cause a dental fluorosis on its own, but it can significantly increase daily F intake. The safety of trace elements in tea is less than factor 1, (i.e., the allowable limit).